1987
DOI: 10.1161/01.hyp.9.6_pt_2.iii31
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A-induced hyperreninemic hypoaldosteronism. A model of adrenal resistance to angiotensin II.

Abstract: SUMMARY We studied the effects of cyclosporin A on the renin-aldosterone axis in SpragueDawley rats. Two weeks of intragastric administration of cyclosporin A (5 mg/kg/day or 20 mg/kg/day) resulted in large increases in plasma renin concentration (23 ± 5, 70 ±12, and 79 ± 11 ng/ml/hr in control rats and rats receiving 5 mg and 20 mg of cyclosporin A, respectively), with no parallel increments in plasma aldosterone. In vitro angiotensin II (ANG II)-stimulated aldosterone secretion by zona glomerulosa cells obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…13 In addition, angiotensin II-stimulated aldosterone secretion is inhibited by PGP modulators in vitro. 14 Studies in rats 15 and humans 16 suggest that the PGP inhibitor cyclosporine A influences the renin-angiotensin-aldosterone system. These experimental results suggest that PGP might play a role in the regulation of the renin-angiotensin-aldosterone system in humans.…”
mentioning
confidence: 99%
“…13 In addition, angiotensin II-stimulated aldosterone secretion is inhibited by PGP modulators in vitro. 14 Studies in rats 15 and humans 16 suggest that the PGP inhibitor cyclosporine A influences the renin-angiotensin-aldosterone system. These experimental results suggest that PGP might play a role in the regulation of the renin-angiotensin-aldosterone system in humans.…”
mentioning
confidence: 99%
“…In addition, mutations in the PGP transmembrane domains 4-6 result in loss of the recognition of steroids with the 17-OH group and the 20-keto oxygen and loss of steroidal effect (34). Hyperreninemic hypoaldosteronism resistant to ANG II stimulation has been reported, in vivo, in rats treated with the PGP substrate cyclosporin A (CSA); the zona glomerulosa cells, isolated from the same animals, also failed to respond to ANG II stimulation (23,28). In humans CSA produces hyperkalemic hyporeninism and a distal tubule defect in K ϩ excretion (16,30).…”
mentioning
confidence: 99%
“…Telmisartan and the prodrug candesartan-cilexetil, angiotensin receptor type 1 blockers, were found to significantly inhibit Pgp activity [121, 122], which implies that important drug-drug inter-actions may occur when these drugs are combined with Pgp substrates. Studies in rats [123] and humans [124] found that the Pgp inhibitor cyclosporine A influences the renin-angiotensin-aldosterone system. Cyclosporine A belongs to the group of calcineurin inhibitors used to induce immuno-suppression after organ transplantation.…”
Section: Selected Vip Genes: Blood Pressure; Salt-sensitivity and Renmentioning
confidence: 99%